Identification of adrenocorticotropin receptor messenger ribonucleic acid in the human pituitary and its loss of expression in pituitary adenomas. - Morris, D; Kola, B; Borboli, N; Kaltsas, G; Gueorguiev, M; McNicol, A; Ferrier, R; Jones, T; Baldeweg, S; Powell, M; Czirják, S; Hanzély, Z; et al. (2003)
The ACTH receptor (ACTH-R) is the second member of the melanocortin (MC-2) receptor family that includes five seven-transmembrane G protein-coupled receptors and has been shown to be predominantly expressed in the adrenal cortex. It has been postulated that ACTH may regulate its own secretion through ultra-short-loop feedback within the pituitary. ACTH-secreting adenomas are characterized by resistance to glucocorticoid feedback, and they may have dysregulated ACTH feedback. We therefore investigated the ACTH-R in normal and adenomatous human pituitary tissue. We report here the identification of ACTH-R mRNA in the human pituitary gland, which was confirmed by direct sequencing. We studied the expression of the ACTH-R in 23 normal pituitary specimens and 53 pituitary adenomas (22 ACTH-secreting, nine GH-secreting, eight prolactin-secreting, one TSH-secreting, one FSH-secreting, 10 nonfunctioning, and two silent corticotroph adenomas), using the sensitive technique of real-time quantitative PCR. Contamination of ACTH-secreting adenomas and nonfunctioning pituitary adenomas with nonadenomatous tissue was excluded by lack of Pit-1 expression. ACTH-R mRNA was detected in all normal pituitary specimens, and in situ hybridization colocalized expression to ACTH staining cells only. However, ACTH-R mRNA levels were undetectable in 16 of 22 ACTH-secreting tumors and in both silent corticotroph tumors. Diagnostic preoperative plasma ACTH levels were significantly lower in the ACTH-R positive ACTH-secreting tumors, compared with those who were ACTH-R negative (P = 0.0006). Direct sequencing of the coding region of the ACTH-R in cDNA from three ACTH-secreting tumors positively expressing the receptor showed no mutations, as did sequencing of genomic DNA in three receptor negative ACTH-secreting tumors and the two silent corticotrophs. These results provide further evidence compatible with an ACTH feedback loop in the pituitary and suggest that loss of expression of the ACTH-R in corticotroph adenomas of patients with Cushing's disease may play a role in the resistance to feedback of the pituitary-adrenal axis seen in these patients.